Circulating Modified Metabolites and a Risk of ESRD in Patients With Type 1 Diabetes and Chronic Kidney Disease - Niewczas, Monika A. (Diabetes Care, 2017)
OBJECTIVE: Patients with type 1 diabetes (T1D) with impaired renal function are at increased risk for end-stage renal disease (ESRD). Although the rate of progression varies, determinants and mechanisms of this variation are unknown. RESEARCH DESIGN AND METHODS: We examined serum metabolomic profiles associated with variation in renal function decline in participants with T1D (the Joslin Kidney Study prospective cohort). One hundred fifty-eight patients with proteinuria and chronic kidney disease stage 3 were followed for a median of 11 years to determine estimated glomerular filtration rate slopes from serial measurements of serum creatinine and to ascertain time to onset of ESRD. Baseline serum samples were subjected to global metabolomic profiling. RESULTS: One hundred ten amino acids and purine and pyrimidine metabolites were detected in at least 80% of participants. Serum levels of seven modified metabolites (C-glycosyltryptophan, pseudouridine, O-sulfotyrosine, N-acetylthreonine, N-acetylserine, N6-carbamoylthreonyladenosine, and N6-acetyllysine) were associated with renal function decline and time to ESRD (P < 0.001) independent of the relevant clinical covariates. The significant metabolites correlated with one another and with the indices of tubular injury. CONCLUSIONS: This prospective cohort study in participants with T1D, proteinuria, and impaired renal function at baseline demonstrated that patients with increased circulating levels of certain modified metabolites experience faster renal function decline, leading to ESRD. Whether some of these candidate metabolites are risk factors or just prognostic biomarkers of progression to ESRD in T1D needs to be determined.